Tradisi Menghiasi Hewan Kurban pada Masyarakat Kenagarian Bawan - Saputra, Edriagus (STAIN Curup, 2019)
Within the millennial era, academics had much discussed the science of living hadith. It even used as one of the supporting knowledge in exploring the traditions in the community. One of them is the tradition of adorning sacrificial animals in Kenagarian Bawan. It carried out before slaughtering the animals. This research explored the tradition by using ethnographic approach in the hadith living. The research found that the community had different understanding about this tradition. Some of them argued that it was a legitimate condition for completing the sacrificial worship since this tradition was an implementation of a hadith of the prophet Muhammad SAW; “... adorn your sacrificial animal because you will ride it at Shirat”. It means to sacrificing the best animal, well selected and decorated, to Allah SWT. The other reason to keep this tradition was because it has done for years.